TINJAUAN PENGLIBATAN PENSYARAH POLITEKNIK DALAM MELAKSANAKAN LATIHAN INOVASI BAGI MENINGKATKAN KUALITI PENGAJARAN DAN PEMBELAJARAN - Muhamad Sanusi, Amanina; Puteh, Saifullizam; Hassan, Nur Farha (Online Journal for TVET Practitioners, 2018)
The involvement of lecturers in implementing innovation in order to improve the quality of teaching and learning is deemed vital in reviewing the level of motivation and technology in educational institutions. This study aims to determine the level of motivation among POLIMAS lecturers’ involvement in teaching and learning training innovation. This study is conducted to aid lecturers in the diversification of technology in teaching and learning by using appropriate technologies. A survey was conducted in order to improve the rate of motivation among lecturers by creating technology facilitated learning environment.